Benign anorectal disorders : a guide to diagnosis and management - Chowdri, Nisar Ahmad; Parray, Fazl Q. (Springer, 2016)
Management of benign anorectal disorders is challenging for the treating surgeons as the patients are highly distressed, the symptoms are always alarming, and surgical intervention may be associated with lifelong disabilities such as loss of sphincter control. Written by highly experienced colorectal surgeons, this book provides detailed notes on optimal management of these disorders including pre- and post-operative management. Chapters cover the entire range of benign disorders such as hemorrhoids, fissure, fistula-in-ano, anorectal injuries, anal incontinence, rectal prolapse, pelvic floor disorders, benign tumors and ulcers, and strictures. Chapters on surgical anatomy and physiology equip the surgeons with the information necessary to understand the complex anatomy and functioning¡of this region which makes surgery all the more difficult. Benign Anorectal Disorders is an essential reading for colorectal surgeons, general surgeons, fellows-in-training and the post-graduate students.